CARDIOVASCULAR DISEASE RISKS AMONG EXTREMELY HIGH HIGH-DENSITY LIPOPROTEIN CHOLESTEROL: LONGITUDINAL STUDY. (16th November 2018) - Kobayashi, D; Asai, K; Noto, H; Takahashi, O; Osugi, Y; Ino, A
Abstract: Background: Previous studies, with one baseline measurement of HDL without considering fluctuation of HDL, suggested that those with extremely high HDL cholesterol had higher cardiovascular mortality. The aim of this study was to evaluate cardiovascular disease incidence among who had extremely high HDL cholesterol compared to those who had normal HDL cholesterol by evaluating time-dependent HDL levels among elderly people in a longitudinal study. Methods: We conducted a retrospective longitudinal study at large academic hospital, Tokyo, Japan, from 2005 to 2016. We included all elderly patients who underwent health check-ups at the center for preventive medicine. Those patients with a prior history of cardiovascular disease were excluded. We categorized patients into 5 groups on the basis of HDL measurements: <40, 40–59, 60–79, 80–89, >90mg/dl. Our primary outcome was the development of cardiovascular disease. Longitudinal analyses by a mixed effect model with time-dependent HDL levels were applied to consider fluctuations in HDL levels within the same patients. Results: 83, 125 participants were included in this study. Median follow-up was 1, 746(Interquartile range (IQR): 2, 375) days, and 1, 896(2.2%) developed cardiovascular diseases. The odds ratios for developing cardiovascular disease was higher among low HDL patients (1.24, 95%CI:1.01–1.54), whereas those were lower among high (0.80, 95%CI:0.71–0.91) or very high HDL (0.71, 95%CI:0.57–0.88) compared to normal HDL population. However, that among extremely high HDL was similar to normal HDL group (OR: 0.95, 95%CI:0.74–1.20). Conclusion: In our longitudinal study, those with extremely high HDL cholesterol had similar risk for cardiovascular diseases compared to those with normal HLD level.